2015
DOI: 10.1007/s00580-015-2108-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of carob powder on lipid profile and histopathology of some organs in rats

Abstract: The present study aimed to investigate the effect of two levels of carob powder 10 and 20 % on lipid profile. Forty male Sprague-Dawley rats were divided into two groups. The first group was fed on a basal diet and acts as a control group. The second group was fed on a hyperlipidemic diet (a basal diet plus 10 % animal fat and 1 % cholesterol). After 6 weeks, the second group was divided into three even subgroups: subgroup 1 was fed on a hyperlipidemic diet, subgroup 2 was fed on a hyperlipidemic diet plus 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…When carob powder was administered to Sprague-Dawley rats along with a hyperlipidemic diet, cholesterol and triglycerides were lessened in a dose-dependent manner [95]. The authors also noted that the histopathological profile of the animal’s heart and kidneys remained normal in those that consumed the carob powder, whereas the rats that followed exclusively the hyperlipidemic diet presented severe abnormalities.…”
Section: Health Benefits Of Carobmentioning
confidence: 99%
“…When carob powder was administered to Sprague-Dawley rats along with a hyperlipidemic diet, cholesterol and triglycerides were lessened in a dose-dependent manner [95]. The authors also noted that the histopathological profile of the animal’s heart and kidneys remained normal in those that consumed the carob powder, whereas the rats that followed exclusively the hyperlipidemic diet presented severe abnormalities.…”
Section: Health Benefits Of Carobmentioning
confidence: 99%
“…The findings also indicate that in carob powder ingested, the histopathological status of the heart, as well as the kidney of the animal while rats who adopted the hyperlipidemic diet had extreme disorders. Carob powder may be a possible choice for an overweight or obese diet (Hassanein et al, 2015). Valero‐Munoz et al found that carob pod fibers have blocked physiological events contributing to atherosclerosis in rabbits with dyslipidemia.…”
Section: Biochemical Applications Of Carobmentioning
confidence: 99%
“…Compared with control, the carob pulp group had significantly lower lipid peroxidation and higher plasma total antioxidant status as well as enhanced catalase (CAT) activity. Accordingly, feeding rats with 10 and 20% carob powder improved the lipid profile and histopathological characteristics in the hearts and kidneys of experimental rats [ 80 ]. El Rabey, Al-Seeni and coworkers observed similar hypo-lipidemic [ 81 ] and antioxidant activities [ 82 ] of methanolic carob powder extracts in hypercholesterolemic rats, although no effects were evident for BW.…”
Section: Effects On Metabolic Healthmentioning
confidence: 99%